279 Correcting Gender Dysphoria –the Anatomical Changes with Male to Female Gender Reassignment Surgery. (1st May 2022) - Attwell-Heap, A; Duncan, C
ABSTRACT: Introduction & Objectives: Increased Global acceptance of transgender communities, gender-affirming genital reconstructive surgery is becoming more prominent. Formalised education and training however has not quite entered the curriculum of many surgical training programs yet it remains imperative we have an understanding of modified anatomy in out patients. We demonstrate anatomical reconstruction during the transition between male to female anatomy. Methods: Patient consent was obtained to take a series of photographs during gender affirming surgery from male to female. Results: Contemporary patients receive both spinal and general anaesthesia prior to positioning in standard lithotomy. A perineal incision of approximately 10cm in the midline raphae exposes the corpora and spongiosum. A simple bilateral orchidectomy was performed at the level of the external inguinal ring. A neovaginal cavity was created by firstly dividing the bulbospongiosus attachments to the perineal body and the space is both blunt and sharply dissected. Further dissection is carried out in the avascular perirectal fat plant anterior to the Denonvilliers fascia. During this dissection a 18-22Fr urethral sound is used to apply downward traction on the rectum. A sterile ultrasound sleeve is placed in the rectum to allow bimanual palpation to confirm intact rectal mucosa. A circumferential incision proximal to the glans is performed to aide degloving of the penis. Bucks fasica is left intact and distal penile skin will later be used to form the clitoral hood. The dorsal neurvascular bundle is raised off the corporal bodies but an attachment to the glans remains. A triangular section of dorsal glans is preserved and dissected off the tips of corpora. The penile tissue is then disassembled separating the corpus spongiosum from the corporal bodies. The corpora are amputated at the level of the pubis, remaining erectile tissue destroyed and oversewn for haemostasis. The Urethra is shortened to an appropriate length to allow the dorsal aspect to align between the neoclitoris and neomeatus. The ventral aspect is spatulated to expose the neomeatus. The penile skin flap is invaginated within the neovaginal space and the skin incised to expose the neoclitoris and neomeatus. The penile skin is then anastomosed to the neoclitoris and neomeatus The distal end of the penile skin flaps is oversewn to create a blind ending tube and thus creating the neovagina. Labia Majora are formed by excising excess scrotal skin to create an appropriate contour. This form of neovagina is compared to methods that involve intestinal and peritoneal lining transfer. Conclusions: We have outline the stepwise transition of male to female anatomy with a conventional contemporary technique. Creation of a neovagina with penile inversion has become common practice in gender affirming surgery. However there are other means of creating genitalia with alternative tissues, which subspecialised practitioners should be aware. Disclosure: Work supported by industry: no.